Knowledge-intensive business services and innovation performance in Brazil - Juliana Bonomi Santos (Innovation & Management Review, 2020)
Purpose - The purpose of this paper is to identify the way different economic sectors in Brazil use knowledge-intensive business services (KIBS) and explore which features of KIBS use are associated with better innovation outcomes. Design/methodology/approach - Clusters and regression analyses were used to analyze data from the national innovation survey (PINTEC) from 2014. Findings - The results show that most of the 55 sectors of the Brazilian economy studied make little use of KIBS, but industries in which firms that interact with KIBS providers also have better innovation performance and offer more innovative offerings. The relationship with higher education institutions and research institutes proved particularly relevant, while the interaction with consultancy firms seems to be a strategy that leaves firms "stuck in the middle". Originality/value - The outcomes confirm the arguments of the literature that the use of KIBS has positive outcomes for customer firms. More importantly, however, the paper complements the existing literature by showing that the type of KIBS used in each country is relevant to understand firms' innovation performance. The outcomes can guide firms and public policy initiatives oriented at the articulation of the national innovation system.
Keywords: 650; Innovation performance; Knowledge-intensive business services (KIBS); KIBS use patterns